Case study: chest physiotherapy as a nursing intervention in a 20- month-old toddler with pneumonia in Padukuhan Bendungan Yogyakarta - Halim, Anzarwati A; Suryani, Suryani (Proceeding International Conference on Health Science and Technology, 2025)
Pneumonia is one of the most common diseases affecting vulnerable groups, particularly toddlers, due to their immature immune systems. This condition can trigger symptoms such as cough, fever, difficulty breathing, and an increased respiratory rate, which are the main clinical signs in children. An effective nursing intervention that can be performed is chest physiotherapy to help remove mucus from the child’s respiratory tract. This study employed a descriptive design with a nursing practice case study approach. The case study focused on examining the respiratory rate (RR) of pediatric patients with respiratory disorders (pneumonia) after undergoing chest physiotherapy techniques effectively for 3×24 hours. After providing health education on pneumonia and demonstrating chest physiotherapy techniques, the evaluation showed an improvement in respiratory function before and after performing chest physiotherapy. The average difference of 5 breaths/minute indicated that chest physiotherapy has an effect in removing sputum, thereby optimizing respiratory ventilation. The implementation of nursing interventions in the form of chest physiotherapy proved effective in helping remove sputum, improving respiratory rate, and enhancing ventilation in children with pneumonia. In addition, providing health education on pneumonia increased the family’s knowledge and skills. This supports both the prevention of recurrence and the management of pneumonia at the family level.